The fine structure of the swine sweat gland. II. The coiled ducts - De Melo, V. R.; Valeri, V.; Orsi, A. M. (My University, 1985)
The duct of the swine sweat gland crosses the dermis and epidermis in sequence. The cells of the dermic segment seem to be related with cellular secretion and absorption. In the epidermic segment of the duct the whole morphology of the cells resembles the cellular morphology of the epidermic cells.
Keywords: animal cell; biopsy; diagnosis; electron microscopy; integument; nonhuman; sweat gland; swine; ultrastructure; Animal; Cell Membrane; Cell Nucleus; Cytoplasm; Microscopy, Electron; Sweat Glands; Swine